A new family placement for Australian blue squill, Chamaescilla: Xanthorrhoeaceae (Hemerocallidoideae), not Asparagaceae - Mclay, Todd G.b.; Bayly, Michael J. (Phytotaxa, 2016)
Chamaescilla is an endemic Australian genus, currently placed in the Asparagaceae, alongside other Australian endemic taxa in the tribe Lomandroideae. A recent molecular phylogeny indicated a relationship with another partly Australian family, the Xanthorrhoeaceae, but was not commented on by the authors. Here we added DNA sequence data for a single Chamaescilla specimen to an alignment representing all families in the Asparagales and performed parsimony and Bayesian phylogenetic analyses. Chamaescilla was strongly resolved as belonging to Xanthorrhoeaceae, subfamily Hemerocallidoideae, alongside two non-Australian members, Simethis and Hemerocallis in the hemerocallid clade. This position is corroborated by morphological characters, including pollen grain shape. We also produced an age-calibrated phylogeny and infer that the geographic distribution of the clade is the result of long distance dispersal between the Eocene and Miocene.